Impact of Covid-19 on incident reporting. (20th October 2021) - Doimo, A; Bianchet, B; Moretti, V; Mellace, F; Favero, B; Longobardi, G; Bellomo, F; Degan, S; Farneti, F; Cocconi, R
Abstract: Background: Incident reporting (IR) is a system of spontaneous and voluntary reporting of events, important for assessing safety risks and for improving safety and quality of care. Since Covid-19 pandemic led to a change on the hospital organization, related to an overload of work and an increase of pressure in the wards, this study aims to evaluate the impact of Covid-19 on IR and on safety culture. Methods: This retrospective study analyzed the data of IR in 2019 and 2020 in the academic hospital of Udine. Number of IR, severity of the events (near miss, events with no harm and events with harm) and IR'S topic were compared. Inappropriate IR were excluded from severity analysis. The chi-square test was used for statistical significance. Results: IR in 2020 showed a reduction of 17.7% compared to 2019 (1097 vs 1334, p < 0, 05). Furthermore, we observed a reduction in near misses (276 vs 390, - 4, 81%, p < 0, 05) and an increase in events with harm (226 vs. 219, + 4, 52%, p < 0, 05). Events with no harm showed no significant increase. The analysis of topics revealed an increase in 2020 of problems concerning assessment of patient (+ 4.47%), especially swab's results delays, organizational aspects (+ 4.88%), due to staff reassignment and ward reorganization, and infection prevention and control (+ 4.65%). This increase is significantly associated with Covid-related IR (p < 0, 05). Conclusions: In 2020 were collected fewer IR than 2019 and with an higher level of severity. This change may be associated to the increased workload of the staff who had less time to report incidents. Nevertheless 2020 showed an increase in reporting Covid-19 related issues concerning delay of diagnostic test, new work condition and infection prevention and control measures. This analysis suggests that the decreased number of IRs and near miss during the first year of the pandemic could represent a reduction in safety culture. Additional data are needed. Key messages: Covid-19 disease influenced the safety culture by reducing the number of IR and near misses reported. New Covid-related issues emerged as critical during the pandemic.